A Hybrid Approach for Complex Industrial Process Monitoring, ISSN / e-ISSN ‎1748-5045 / 1748-5045 - Rezki Nafissa; Kazar Okba; Mouss Leila Hayet; Kahloul Laid (Journal of scientific and industrial research, 2017)
This study proposes a multi-agent system with several intelligences for complex industrial process monitoring. The suggested multi-agent system combines a set of techniques which are: multivariate control charts, neural networks, and Bayesian networks. The proposed approach has been evaluated on the TEP (Tennessee Eastman Process). The obtained results have been compared with set of methods that were applied to the Tennessee Eastman Process in the literature; our system performs better on the faults diagnosis.